Application of the rigid finite element method to static analysis of lattice-boom cranes - Adamiec-Wójcik, Iwona; Drąg, Łukasz; Wojciech, Stanisław; Metelski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
In the paper a nonlinear model of a lattice-boom crane with lifting capacity up to 700mT for static analysis is presented. The rigid finite element method is used for discretisation of the lattice-boom and the mast. Flexibility of rope systems for vertical movement and for lifting a load is also taken into account. The computer programme developed enables forces and stress as well as displacements of the boom to be calculated. The model is validated by comparison of the authors? own results with those obtained using professional ROBOT software. Good compatibility of results has been obtained.
Keywords: rigid finite element method; static analysis; lattice-boom crane; flexibility of rope systems